2000
DOI: 10.1038/sj.onc.1204006
|View full text |Cite
|
Sign up to set email alerts
|

Reduced mammary tumor progression in WAP-TAg/WAP-maspin bitransgenic mice

Abstract: Maspin is a unique serpin involved in the suppression of tumor growth and metastasis. To investigate whether increased levels of maspin protect against tumor progression in vivo, we established a transgenic model in which maspin is targeted to mammary epithelial cells by the Whey Acidic Protein (WAP) promoter for overexpression. We crossed these WAP-maspin transgenic mice with the WAP-TAg mouse model of tumor progression. Maspin overexpression increased the rate of apoptosis of both preneoplastic and carcinoma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
53
0
3

Year Published

2000
2000
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(59 citation statements)
references
References 22 publications
3
53
0
3
Order By: Relevance
“…Moreover, ETS motifs are frequently located in the vicinity of the transcription start site in a number of promoters that lack a TATA element, including the genes encoding DNA polymerase a and b (Pearson et al, 1991;Yamaguchi et al, 1988), thymidilate synthetase (Jolli and Johnson, 1991), von Willebrand factor (Schwachtgen et al, 1998), Ets2 (Mavrothalassitis et al, 1990, the tumor suppressor gene Maspin (Zhang et al, 1997) and number of myeloid speci®c genes (reviewed by Moreau-Gachelin, 1994). It seems that PARP can be added to this group of genes because it exhibits features typical of TATA-de®cient promoters and has consensus ETS motifs close to the major initiation sites.…”
Section: Inhibition Of Ets1 Expression Enhances Growth Retardation Ofmentioning
confidence: 99%
“…Moreover, ETS motifs are frequently located in the vicinity of the transcription start site in a number of promoters that lack a TATA element, including the genes encoding DNA polymerase a and b (Pearson et al, 1991;Yamaguchi et al, 1988), thymidilate synthetase (Jolli and Johnson, 1991), von Willebrand factor (Schwachtgen et al, 1998), Ets2 (Mavrothalassitis et al, 1990, the tumor suppressor gene Maspin (Zhang et al, 1997) and number of myeloid speci®c genes (reviewed by Moreau-Gachelin, 1994). It seems that PARP can be added to this group of genes because it exhibits features typical of TATA-de®cient promoters and has consensus ETS motifs close to the major initiation sites.…”
Section: Inhibition Of Ets1 Expression Enhances Growth Retardation Ofmentioning
confidence: 99%
“…Accumulative evidence demonstrates that maspin inhibits the progression of prostate and breast tumors at the late stages of invasion and metastasis [1,7,[9][10][11][12]. In several mammary carcinoma cell lines, maspin is undetectable or is expressed at very low levels [1].…”
Section: Introductionmentioning
confidence: 99%
“…In primary breast cancer cells, maspin is down-regulated and its expression is inhibited in metastasis. It has been suggested that this decrease in maspin expression may be due to the absence of transactivation through the Ets and Ap1 elements in the promoter of maspin (Zhang et al, 1997a). Another report showed that expression of maspin can also be repressed by a negative hormonal response element in the prostate cells (Zhang et al, 1997b).…”
Section: Introductionmentioning
confidence: 99%